The Problem Of Scientific Personnel Training At The Uzbekistan Academy Of Sciences - Ismailov Alisher (Zien Journals, 2022)
This article focuses on the issue of personnel training in the system of the Academy of Sciences of the Republic of Uzbekistan. It analyzed the attitude to personnel, personnel training mechanism, social protection and support processes.
Keywords: Academy of Sciences; social protection; mechanism; principles